2003
DOI: 10.1007/s00438-003-0829-z
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of DNA methylation in Arabidopsis thaliana based on methylation-sensitive AFLP markers

Abstract: The online version of the original article can be found at http:// dx.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
76
1
3

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 52 publications
(85 citation statements)
references
References 0 publications
5
76
1
3
Order By: Relevance
“…The potential link between natural epigenetic variation and phenotypic variability observed in trees is further supported by studies in ecotypes and individual populations of specific herbaceous plant species (Cervera et al 2002;Marfil et al 2009). Highly conserved DNA methylation patterns were detected within an A. thaliana ecotype (Ler) while clear DNA methylation differences existed between ecotypes that did not correlate with nucleotide sequence variation, but with their flowering time (Cervera et al 2002). Furthermore, variation in the floral phenotype of individuals from a single natural population of a wild hybrid potato (Solanum ruiz-lealii) was found to correlate with distinct DNA methylation patterns, but not with DNA sequence variation (Marfil et al 2009).…”
Section: Epigenetic and Phenotypic Variation In Natural Populations mentioning
confidence: 93%
See 1 more Smart Citation
“…The potential link between natural epigenetic variation and phenotypic variability observed in trees is further supported by studies in ecotypes and individual populations of specific herbaceous plant species (Cervera et al 2002;Marfil et al 2009). Highly conserved DNA methylation patterns were detected within an A. thaliana ecotype (Ler) while clear DNA methylation differences existed between ecotypes that did not correlate with nucleotide sequence variation, but with their flowering time (Cervera et al 2002). Furthermore, variation in the floral phenotype of individuals from a single natural population of a wild hybrid potato (Solanum ruiz-lealii) was found to correlate with distinct DNA methylation patterns, but not with DNA sequence variation (Marfil et al 2009).…”
Section: Epigenetic and Phenotypic Variation In Natural Populations mentioning
confidence: 93%
“…Despite the substantial impact that epigenetics might have in determining environmental compatibility, relatively few studies have investigated the extent of natural epigenetic variation and its relationship to phenotypic variation and adaptation potential (Cervera et al 2002;Bossdorf et al 2008;Jablonka and Raz 2009;Marfil et al 2009;Herrera and Bazaga 2010;Lira-Medeiros et al 2010;Paun et al 2010). Among the different epigenetic mechanisms that are potentially involved in transgenerational inheritance and natural epigenetic variation, DNA methylation represents the most-studied modification (Akimoto et al 2007;Jablonka and Raz 2009;Herrera and Bazaga 2010;Lira-Medeiros et al 2010;Paun et al 2010;Verhoeven et al 2010).…”
Section: Epigenetic and Phenotypic Variation In Natural Populations mentioning
confidence: 99%
“…Cubas et al 1999;Cervera et al 2002;Riddle & Richards 2002;Keyte et al 2006;Shindo et al 2006;Vaughn et al 2007). For instance, Cervera et al (2002) and Vaughn et al (2007) found large and consistent ecotypic variation of DNA methylation in A. thaliana that was not correlated with genetic variation. Keyte et al (2006) explored DNA methylation polymorphism in 20 accessions of cotton and found that the levels of epigenetic variation greatly exceeded genetically based estimates of variation.…”
Section: The Epigenetic Codementioning
confidence: 99%
“…Another important insight from recent epigenetics research is that there can be natural variation in epigenetic modifications that is at least partly independent from variation in the DNA sequence (e.g. Cubas et al 1999;Cervera et al 2002;Riddle & Richards 2002;Keyte et al 2006;Shindo et al 2006;Vaughn et al 2007). For instance, Cervera et al (2002) and Vaughn et al (2007) found large and consistent ecotypic variation of DNA methylation in A. thaliana that was not correlated with genetic variation.…”
Section: The Epigenetic Codementioning
confidence: 99%
See 1 more Smart Citation